Frequent position of third mandibular molars, according to Pell and Gregory classification in panoramic x - rays at the -ZERO, Huancayo 2018 - Apumayta De La Cruz, Flor de María (2020)
Objective: To determine the most frequent position of third mandibular molars, according to Pell and Gregory classification in panoramic x - rays at the -ZERO, Huancayo 2018. Material and methods: Regarding the methodology used by the sequence of studies period, it is retrospective crosssectional and according to its level it was descriptive. The sample was not probabilistic, for convenience, consisting of 396 panoramic radiographs in an age range of 18 to 40 years. Results: A total 792 third mandibular molars, excluding missing parts, there is a higher prevalence of class II position B with 37.5 percent (n = 297), followed by class II position A with 22.5 percent (n = 178) and class I position A with 18.8 percent (n = 149) of the total. Conclusions: There is a higher prevalence of class II position B, in both sexes and in most age groups in the panoramic x-rays evaluated.